Molecular variability in Amerindians: widespread but uneven information - Francisco M. Salzano (Anais da Academia Brasileira de Ciências, 2002)
A review was made in relation to the molecular variability present in North, Central, and South AmericanIndian populations. It involved results from ancient DNA, mitochondrial DNA in extant populations, HLAand other autosomal markers, X and Y chromosome variation, as well as data from parasitic viruses whichcould show coevolutionary changes. The questions considered were their origin, ways in which the earlycolonization of the continent took place, types and levels of the variability which developed, peculiaritiesof the Amerindian evolutionary processes, and eventual genetic heterogeneity which evolved in differentgeographical areas. Although much information is already available, it is highly heterogeneous in relation topopulations and types of genetic systems investigated. Unfortunately, the present trend of favoring essentiallyapplied research suggest that the situation will not basically improve in the future.